Phenotypic Detection and Antibiotic Resistance Pattern of AmpC b-lactamase Producers among the Gram-Negative Uropathogens at A Tertiary Care Hospital - Akter, Dilruba; Rashid, Md Mahbubur; Akter, Sharmin; Begum, Shaila; arim Chowdhury, Abu Hena Md. Saiful K; Ahmed, Md Shakeel (Journal of Chittagong Medical College Teachers’ Association, 2022)
Background: An increase in the incidence of Urinary Tract Infections (UTI) leads to more consumption of antimicrobials and increases the chances of resistance among organisms. The objective of this study was to understand the prevalence of AmpC β-lactamase producing gram-negative uropathogens by using the inhibitor-based method and their antimicrobial susceptibility pattern. Materials and methods: The cross-sectional study was conducted in 2015 and urine samples were collected from patients at a medical college hospital. Identification of gramnegative uropathogens was done by standard laboratory methods of identification and screened for AmpC betalactamase production by cefoxitin disc. AmpC b-lactamase producing organisms were confirmed by phenotypic inhibitor-based combined disc diffusion method. Results: Out of 280 urine samples, 120 (42.9%) were culture positive, and among them, 118 (98.3%) organisms were gram-negative bacteria and 2 (1.7%) were grampositive bacteria. Among the gram-negative bacteria, the majority were E. coli (40.7%), Klebsiella spp. (33.9%), Pseudomonas spp. (22.9%), followed by Proteus spp., Acinetobacter spp., and Serratia spp. (2.4%). Among the isolated bacteria, 48 (40.7%) were AmpC b-lactamase producers and they showed high degree of resistance to amoxiclav (100.0%) cefotaxime (95.8%) ceftazidime (87.5%) nalidixic acid (85.4%) ceftriaxone (81.3%) cefepime (75.0%) aztreonam (70.8%) co-trimoxazole (68.8%) nitrofurantoin (66.7%) ciprofloxacin (58.3%) etc. Conclusion: Antimicrobial resistance among AmpC blactamase producing bacterial pathogens was considerably high which underscores the need of updating UTI guidelines and surveillance. The inhibitor-based combined disc diffusion method can be used as a simple, cheap and rapid phenotypic test for the detection of AmpC blactamase in clinical laboratories. JCMCTA 2022 ; 33 (2) : 8-13